Pengaruh Demografi Terhadap Tingkat Pengetahuan Penanganan Nyeri Dalam Penggunaan Obat Tanpa Resep Pada Masyarakat Desa Donokerto - Viviane Annisa; Aisya Aprilia Handari; Ardiya Frida Hanifah; Arikah Syahbani; Chairunisa Shinta Indarwati; Dewi Nur Umiaroh; Irma Arya Wandani Rusdiana; Luthfiana Qurrotuaini; Nonik Indrian Lestari; Ravi Antonio Belva; Tasha Rahmadona (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
The main problem faced by the Donokerto Village community is the low level of public literacy regarding the safe use of over-the-counter medications, appropriate dosages, and awareness of consulting with health professionals. This community service program aims to increase public understanding of how to manage pain using over-the-counter medications through the SIPENA (Pharmacy Cares for Your Pain) program. The program was carried out through direct outreach activities that included a pre-test, distribution of educational leaflets, interactive lectures, question-and-answer discussions, and a post-test. The results showed an increase in the average knowledge score from 11.5 to 14.1 after the outreach. This proves that the outreach was effective for all groups. In conclusion, the SIPENA program successfully increased health literacy and public awareness about the rational use of pain medication.